Redesign of The Digital Population Identity Application (DPIA) Interface Using Design Thinking to Improve User Experience - Muhammad Zaki Robbi Akhsin; Kurniawan Dwi Irianto (International Journal Software Engineering and Computer Science (IJSECS), 2025)
The objective of the study is to enhance user experience within the Digital Population Identity Application (DPIA), known as Identitas Kependudukan Digital (IKD), through interface redesign for public administration services in Indonesia. The research employs a user-centered design methodology structured around five sequential phases: user experience analysis, challenge identification, solution ideation, prototype development, and evaluation testing. Data collection involves user interviews and direct observation of application usage patterns. The application prototype underwent redesign based on identified challenges and was subsequently evaluated through quantitative survey methods focusing on usability metrics. Post-redesign testing revealed substantial improvements in ease of use, navigation efficiency, and user comfort levels. The study outcomes aim to advance user-friendly public service applications and may serve as a framework for developing additional digital systems requiring direct community-government interaction.